Perceptions of teachers in implementing simulation games in the teaching and learning of Geography at Zimbabwe Junior Certificate Level: a case of Wedza Rural District Secondary Schools - Muskwe, Shelly (Midlands State University, 2014)
This study examined the perceptions of teachers in implementing simulation games in teaching and learning of Geography at Zimbabwe Junior Certificate Level in Wedza District secondary schools. The problem was that teachers were not using simulation games in teaching and learning of Geography at ZJC. The study, therefore, investigated the perceptions of teachers and challenges faced by teachers in implementing simulation games. The study also looked at possible ways to improve the use of simulation games. A critical literature review was done which revealed that teachers have positive perceptions of simulation games. The literature also revealed that teachers are facing challenges such as lack of teacher training and professional development on the use of simulation games to equip them with skills necessary for successful implementation. The study employed the descriptive research design. The population comprised 10 secondary schools. A sample of three schools was randomly selected which consisted of one Mission Boarding School, one Government High School and one Community Secondary School. Purposive sampling technique was used to select five ZJC Geography teachers, 3 heads of Geography department and 3 heads of schools to serve as informants. Students were selected using stratified random sampling technique. Self structured likert scale questionnaires of teachers and students and interviews of heads of schools, heads of Geography department and ZJC Geography teachers were employed for the purpose of collecting data. The content analysis method was used for data analysis. The results showed that teachers had positive perceptions of simulation games. However they are facing challenges such as lack of adequate simulation games technologies and lack of funds to purchase these technologies in order to successfully implement simulation games in teaching and learning. The study recommended that students be exposed to learning with simulation games as they have positive impacts on students’ learning. Other recommendations were that availability of simulation games technologies and access to these technologies be improved in order for teachers to successfully implement simulation games in teaching and learning.